Magnitude of Induced Abortion and Associated Factors among Female Students of Hawassa University, Southern Region, Ethiopia, 2019 - Addisu Tadesse Sahile; Mieraf Shiferaw Beyene (Hindawi Limited, 2020)
Objectives. This study was aimed at assessing the magnitude of induced abortion and associated factors among students in Hawassa University, southern region, Ethiopia, 2019. Methods. An institutional-based cross-sectional study was conducted among a total of 422 students selected on the bases of a probability simple random sampling method. A pretested structured questionnaire was used to collect data. Analysis was made with SPSS 20. Descriptive summary and inferential statistics (binary logistic regression) were used with a 95% CI and P value of less than 5% as a level of significance. Findings were presented in tables, figure, and texts. Confidentiality of information was also secured. Results. The prevalence of induced abortion in the study setting was 68.7% (95% CI: 64.15%-73.2%). Participants who used emergency contraceptives had 12 times higher odds of undergoing abortion than those who did not use emergency contraceptives at AOR: 11.95, 95% CI: 5.615-25.326, P<001. Conclusions. A higher prevalence of induced abortion was observed in the study setting. Contraceptive use was the predictor of induced abortion identified. Concerned bodies were recommended to work on the identified determinant of induced abortion in the study setting.